Early Ibadi Theology: New Material on Rational Thought in Islam from the Pen of al-Fazārī (2nd/8th Century) - al-Salimi, Abdulrahman, (Islamic History and Civilization ;, 2021)
Al-Fazārī's writings are a unique source of information about Ibadi teachings on ʿilm al-kalām and the early development of this branch of religious knowledge. It is for this reason that scholars of Islamic theology are particularly interested in early Ibadi theology. In this volume newly discovered, re-edited texts by al-Fazārī are presented, with previously lacking fragments included, texts that had already begun to offer new perspectives on Islamic ʿilm al-kalām , and on its origins and the sources of its concepts and debating techniques. In their revised state these Ibadi texts represent a major contribution to scholastic theology. They demonstrate how their respective theological debates already took place at the beginning of the second/eighth century and how associated ideas, as well as related sects and treatises, remained current for some time afterwards, thereby contradicting earlier claims that these debates started in the third/ninth century.